Magnetic nano demulsifier as well as preparation method and application thereof
A polydopamine-modified Fe3O4 nanoparticle-based magnetic nano-emulsifier addresses the inefficiencies of conventional demulsifiers by forming stable surfactant layers, achieving high demulsification efficiency and recyclability, suitable for oil-water separation applications.
Patent Information
- Application Number
- CN202411224537.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2024-12-31
AI Technical Summary
Conventional demulsifiers, particularly block polyether demulsifiers, suffer from low demulsification efficiency and long demulsification times, and recycled magnetic nano demulsifiers face issues with surfactant layers easily detaching, leading to poor recovery performance.
A method involving the use of polydopamine-modified Fe3O4 nanoparticles, combined with block polyether under UV irradiation, forms a stable and reusable magnetic nano-emulsifier by bonding amino groups and catechol in polydopamine molecules to the nanoparticle surface, enhancing surface activity and adhesion.
The novel magnetic nano-emulsifier achieves high demulsification efficiency of up to 99.5% and can be recycled up to 8 times, offering improved efficiency and stability in oil-water separation.
Smart Images

Figure CN119215486A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of oil-water emulsion demulsification, and in particular to a magnetic nano demulsifier and a preparation method and application thereof. Background Art
[0002] As the "blood of industry", petroleum has always been an important support for the survival and development of human society. However, with the continuous deepening of oil field exploitation and the promotion and use of secondary or tertiary oil recovery technology, the water content in the oil-water emulsions produced during the exploitation of major oil fields has continued to increase, resulting in serious emulsification. Improper treatment will cause serious pollution to the environment. At present, among the treatment methods of oil-water emulsions, chemical demulsification (surfactant) is the mainstream treatment method for oil-water emulsions. Chemical demulsifiers mainly include anionic demulsifiers, cationic demulsifiers and non-ionic demulsifiers, among which non-ionic demulsifiers are the most widely used. There are many types of block polyether demulsifiers in non-ionic demulsifiers and the demulsification effect is good. However, block polyether demulsifiers have the defect that they cannot be recycled.
[0003] With the rapid development of nanomaterial technology, various nanomaterial-based treatment agents are widely used in the petrochemical industry. Nanomaterials with large specific surface area have special effects such as surface effect, macroscopic quantum tunneling effect, and quantum size effect. Among them, the surface effect of nanomaterials refers to the increase in the surface energy of solid particles when the radius of solid particles is reduced to the nanoscale and the specific surface area is increased, making them exhibit strong chemical properties and strong adsorption properties. Based on this characteristic of nanomaterials, researchers in the field of oil-water separation in petrochemicals have conducted research on nanomaterials. According to the presence or absence of magnetism, nano demulsifiers are divided into magnetic nano demulsifiers and non-magnetic nano demulsifiers. Compared with non-magnetic nano demulsifiers, magnetic nano demulsifiers not only have excellent chemical properties and adsorption properties, but can also be reused through magnetic recovery, so they have more application prospects. However, the conventional demulsifiers on the market currently have low demulsification efficiency and long demulsification time for oil-water emulsions. Therefore, it is necessary to explore a magnetic nano demulsifier with high demulsification efficiency. Summary of the invention
[0004] The present disclosure provides a magnetic nano-emulsifier and a preparation method and application thereof, so as to at least solve the above technical problems existing in the prior art.
[0005] Ferroferric oxide (Fe3O4) particles have the characteristics of simple preparation, low cost and good compatibility, but the demulsification performance of single nano-Fe3O4 is not strong. Some studies have compounded functionalized carbon nanotubes (CNTs) and ferroferric oxide, and prepared magnetic demulsifier CNTs / Fe3O4 by solvent thermal method. The demulsification efficiency can still reach 91.43% when recycled 4 times. There are also studies on grafting polyethyleneimine (PEI) on magnetized demulsifiers to increase the functional groups on the surface of magnetic particles to prepare Fe3O4-PEI magnetized demulsifiers. After settling for 2h, the demulsification efficiency can still reach 98.3%. However, the above demulsifiers all have the problem that the modified layer is easy to fall off, resulting in poor recovery performance. Based on this, the present disclosure proposes the following scheme.
[0006] According to a first aspect of the present disclosure, a method for preparing a magnetic nano-emulsifier is provided, comprising the following steps:
[0007] S1: dissolving polydopamine (PDA) in phosphate buffer (PS) to obtain polydopamine phosphate; mixing the polydopamine phosphate with Fe3O4, and stirring in the dark and aerobic conditions to obtain a Fe3O4@polydopamine complex;
[0008] S2: dissolving the Fe3O4@polydopamine complex obtained in step S1 in a phosphate buffer solution, then mixing it with a block polyether, and stirring it under ultraviolet light irradiation and aerobic conditions to obtain the magnetic nano-emulsifier.
[0009] In one embodiment, the phosphate buffer solution is prepared as follows: disodium hydrogen phosphate and sodium dihydrogen phosphate are dissolved in water to obtain the phosphate buffer solution.
[0010] In one embodiment, the pH of the phosphate buffer is 8.3-8.5.
[0011] In a preferred embodiment, the pH of the phosphate buffer is 8.5.
[0012] In one embodiment, the mass volume ratio of the polydopamine to the phosphate buffer in step S1 is 0.1-0.2 g:400 mL.
[0013] In one embodiment, the mass ratio of the polydopamine to the Fe3O4 in step S1 is 1:1-3.
[0014] In one embodiment, in step S1, after mixing the polydopamine phosphate and the Fe3O4, ultrasonic dispersion is first performed for 5 to 8 minutes, and then the stirring is performed.
[0015] In one embodiment, the stirring conditions in step S1 include: stirring at a speed of 100 to 300 r / min for 12 to 36 hours in the dark and in the presence of oxygen.
[0016] In one embodiment, after the stirring, step S1 further comprises the following steps: washing the product obtained after stirring with ethanol and water alternately three times, and then performing magnetic separation to obtain the Fe3O4@polydopamine complex.
[0017] In one embodiment, the mass volume ratio of the Fe3O4@polydopamine complex to the phosphate buffer in step S2 is 0.1-0.3 g:200 mL.
[0018] In one embodiment, the mass ratio of the Fe3O4@polydopamine complex to the block polyether in step S2 is 1:1-3.
[0019] In one embodiment, the block polyether is selected from at least one of a polyol block polyether and a polyamine block polyether.
[0020] Specifically, block polyether is a homopolymer long chain segment formed by ethylene oxide (EO) and propylene oxide (PO), which are arranged at intervals on the main chain. The ratio of EO / PO is not limited and can be set according to specific application conditions. Generally, high EO content means strong hydrophilicity; high PO content means strong lipophilicity.
[0021] In a preferred embodiment, the block polyether is selected from ethylenediamine block polyether.
[0022] In one embodiment, the stirring conditions in step S2 include: stirring at a speed of 100 to 300 r / min for 1 to 3 hours under ultraviolet light irradiation and aerobic conditions.
[0023] In one embodiment, after the stirring, step S2 further comprises the following steps: washing the product obtained by stirring with ethanol and water alternately three times, and then performing magnetic separation to obtain the magnetic nano-emulsifier.
[0024] According to a second aspect of the present disclosure, a magnetic nano-emulsifier prepared according to the above preparation method is provided.
[0025] According to a third aspect of the present disclosure, there is provided a use of the magnetic nano-emulsifier in the treatment of oil-water emulsions.
[0026] According to an implementation method of the present disclosure, at least the following beneficial effects are achieved:
[0027] 1. This invention discloses for the first time the use of biomimetic polydopamine adhesion surfactant (block polyether) on magnetic nanoparticles (Fe3O4) to modify the surface of magnetic nanoparticles. This method has the advantages of simple operation, mild conditions, short preparation cycle and no pollution.
[0028] 2. The present invention discloses a functional design of polydopamine-adhered magnetic nanoparticles, wherein the amino group and catechol in the polydopamine molecule are simultaneously bonded to the surfactant by forming hydrogen bonds, thereby firmly fixing the surfactant on the surface of the magnetic nanoparticles, achieving surface activity modification to increase the surface wettability of the magnetic demulsifier, and preventing the surfactant from falling off, thereby improving the reuse rate of the magnetic nano demulsifier.
[0029] 3. Different from the traditional polydopamine modification, the present invention introduces UV-assisted modification, which greatly saves the modification time and modification cost.
[0030] 4. The novel bionic magnetic nano-demulsifier prepared by the present invention can be well adsorbed at the oil-water interface to form a variety of arrangement structures to break the oil-water interface and achieve oil-water two-phase separation; after demulsification, it can be recovered through the action of the magnetic field to achieve the recycling of the demulsifier. It can be seen that the magnetic nano-demulsifier disclosed in the present invention has excellent demulsification efficiency and recyclability, and its demulsification efficiency can reach up to 99.5%, and it can be recycled and used 8 times with a demulsification efficiency of more than 99%.
[0031] 5. The novel bionic magnetic nano-emulsifier prepared in the present invention has important application value and development potential in the field of emulsified oil treatment due to its high efficiency, stability, environmental protection and broad application prospects.
[0032] It should be understood that the content described in this section is not intended to identify the key or important features of the embodiments of the present disclosure, nor is it intended to limit the scope of the present disclosure. Other features of the present disclosure will become easily understood through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The above and other objects, features and advantages of the exemplary embodiments of the present disclosure will become readily understood by reading the detailed description below with reference to the accompanying drawings. In the accompanying drawings, several embodiments of the present disclosure are shown in an exemplary and non-limiting manner, in which:
[0034] In the drawings, the same or corresponding reference numerals represent the same or corresponding parts.
[0035] Figure 1 The schematic diagram of the preparation process of the magnetic nano-emulsifier in Example 1 of the present disclosure is shown;
[0036] Figure 2Transmission electron micrographs of Fe3O4, Fe3O4@PDA and Fe3O4@PDA-EDEP in Example 1 of the present disclosure are shown; wherein, (a1) to (a3) are transmission electron micrographs of Fe3O4; (b1) to (b3) are transmission electron micrographs of Fe3O4@PDA; (c1) to (c3) are transmission electron micrographs of Fe3O4@PDA-EDEP;
[0037] Figure 3 Fourier transform infrared spectra of Fe3O4, Fe3O4@PDA and Fe3O4@PDA-EDEP in Example 1 of the present disclosure are shown;
[0038] Figure 4 The demulsification efficiency diagram of the magnetic nano-demulsifiers Fe3O4@PDA-EDEP and Fe3O4@PDA at different concentrations in Example 1 and Comparative Example 1 of the present disclosure is shown;
[0039] Figure 5 The demulsification efficiency diagram of the magnetic nano demulsifier in Example 1 of the present disclosure and Comparative Example 1 after 10 times of recycling is shown. DETAILED DESCRIPTION
[0040] In order to make the purpose, features, and advantages of the present disclosure more obvious and easy to understand, the technical solutions in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the drawings in the embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present disclosure.
[0041] Example 1
[0042] This example prepares a magnetic nano-emulsifier. The preparation process is shown in Figure 1 The specific process is as follows:
[0043] (1) 6.76 g of disodium hydrogen phosphate and 0.288 g of sodium dihydrogen phosphate were stirred in 100 mL of ultrapure water until dissolved, and the mixture was placed in a 1 L volumetric flask, and the volume was adjusted to 1 L with ultrapure water to prepare a phosphate buffer (PS) solution with a pH of 8.5. The solution was set aside for future use, and the shelf life was two weeks.
[0044] (2) 0.1 g of polydopamine (PDA) was added to 400 mL of PS solution and stirred to dissolve to obtain polydopamine phosphate; then 0.1 g of Fe3O4 was added and ultrasonically dispersed for 5 min. The mixture was stirred at 200 r / min for 24 h in the dark and under aerobic conditions. After washing three times with ethanol and water alternately, the Fe3O4@PDA complex (i.e., Figure 1The Fe3O4@PDA) was dried in vacuum at 45 °C for 2 h and stored for later use.
[0045] (3) 0.1 g of Fe3O4@polydopamine complex was added to 200 mL of PS solution and stirred evenly, and 0.1 g of ethylenediamine block polyether (EDEP) was added. The mixture was stirred at 200 r / min for 2 h under 365 nm ultraviolet light irradiation and aerobic conditions. The mixture was washed alternately with ethanol and water three times, and then a magnetic nano-emulsifier (i.e., Figure 1 The Fe3O4@PDA-EDEP) was dried in vacuum at 45°C for 2 h and stored for later use.
[0046] Example 2
[0047] This example prepares a magnetic nano-emulsifier, and the specific process is as follows:
[0048] (1) 6.76 g of disodium hydrogen phosphate and 0.288 g of sodium dihydrogen phosphate were stirred in 100 mL of ultrapure water until dissolved, and the mixture was placed in a 1 L volumetric flask, and the volume was adjusted to 1 L with ultrapure water to prepare a phosphate buffer (PS) solution with a pH of 8.5. The solution was set aside for future use, and the shelf life was two weeks.
[0049] (2) 0.2 g of polydopamine (PDA) was added to 400 mL of PS solution and stirred to dissolve to obtain polydopamine phosphate; then 0.3 g of Fe3O4 was added and ultrasonically dispersed for 5 min. The mixture was stirred at 200 r / min for 24 h in the dark and under aerobic conditions. After washing three times with ethanol and water alternately, the Fe3O4@polydopamine complex was prepared by magnetic separation, vacuum dried at 45°C for 2 h, and stored for later use.
[0050] (3) 0.2 g of Fe3O4@polydopamine complex was added to 200 mL of PS solution and stirred evenly. 0.3 g of ethylenediamine block polyether (EDEP) was added and stirred at 200 r / min for 2 h under 365 nm ultraviolet light and aerobic conditions. The mixture was washed alternately with ethanol and water three times, and then a magnetic nano-emulsifier was prepared by magnetic separation. The mixture was vacuum dried at 45 °C for 2 h and stored for later use.
[0051] Comparative Example 1
[0052] This comparative example prepares a magnetic nano-emulsifier, which is different from Example 1 in that the magnetic nano-emulsifier prepared in this comparative example is not modified by a surfactant, that is, Fe3O4@PDA. The specific process is as follows:
[0053] (1) 6.76 g of disodium hydrogen phosphate and 0.288 g of sodium dihydrogen phosphate were stirred in 100 mL of ultrapure water until dissolved, and the mixture was placed in a 1 L volumetric flask, and the volume was adjusted to 1 L with ultrapure water to prepare a phosphate buffer (PS) solution with a pH of 8.5. The solution was set aside for future use, and the shelf life was two weeks.
[0054] (2) 0.1 g of polydopamine was added to 400 mL of PS solution and stirred to dissolve to obtain polydopamine phosphate; then 0.1 g of Fe3O4 was added and ultrasonically dispersed for 5 min. The mixture was stirred at 200 r / min for 24 h in the dark and under aerobic conditions. After washing three times with ethanol and water alternately, Fe3O4@polydopamine complex (i.e., Fe3O4@PDA) was prepared by magnetic separation, vacuum dried at 45°C for 2 h, and stored for later use.
[0055] Test example
[0056] 1. The morphology of Fe3O4, Fe3O4@PDA and Fe3O4@PDA-EDEP in the process of preparing magnetic nano-emulsifier in Example 1 was observed by transmission electron microscopy. Figure 2 shown. Figure 2 The results show that the original Fe3O4 nanoparticles have irregular morphology and sizes ranging from 100nm to 500nm; the dispersion of Fe3O4 nanoparticles is poor and agglomeration occurs (e.g. Figure 2 (a1)~(a3)). After the surface modification by polydopamine, a layer of polydopamine is attached to the surface of Fe3O4 nanoparticles, and the thickness of the polydopamine layer is about 100nm to 200nm (e.g. Figure 2 (b1)~(b3)), since the polydopamine layer is amphiphilic and has secondary adhesion, it provides a certain steric hindrance to the surface of Fe3O4 nanoparticles and is conducive to further modification. After EDEP modification, the dispersibility of Fe3O4@PDA-EDEP (magnetic nanoemulsifier) is further improved, which will be more beneficial for its dispersion in the oil-water amphiphilic interface and improve the demulsification efficiency (such as Figure 2 (c1)~(c3)).
[0057] 2. Fourier transform infrared spectroscopy (FT-IR) tests were performed on Fe3O4, Fe3O4@PDA and Fe3O4@PDA-EDEP in the process of preparing magnetic nano-emulsifier in Example 1. The results are as follows: Figure 3 shown. Figure 3 It is shown that in Fe3O4, 3426.08cm -1 The characteristic peak at 583.99 cm is the stretching vibration peak of hydroxyl group. -1The characteristic peak at 577.17 cm belongs to the stretching vibration peak of the strong Fe-O absorption band. After polydopamine was loaded on the Fe3O4 surface, it did not cover the stretching vibration peak of the Fe-O bond of Fe3O4, but only slightly shifted. -1 , 1289.06cm -1 and 1602.37cm -1 The characteristic peaks at 3209.84 cm are the COC stretching vibration and C-CH2 stretching vibration of polydopamine. -1 The characteristic peak at 1289.06cm is the stretching vibration of NH. This indicates the successful loading of polydopamine nanolayer on the Fe3O4 surface. After further modification by EDEP, -1 and 1602.37cm -1 The characteristic peak at 1348.40 cm -1 and 1606.97cm -1 In addition, the stretching vibration peak of NH shifted to 3384.62 cm -1 , analysis showed that the amino groups on EDEP and polydopamine were strongly hydrogen-bonded, proving that EDEP was successfully modified onto the surface of Fe3O4@PDA.
[0058] 3. Prepare 5wt% diesel emulsion (a mixture of diesel and water), and use the bottle test method to evaluate the demulsification performance of the magnetic nano demulsifier prepared in Example 1 and Comparative Example 1. First, add 40mL of diesel emulsion into 100mL numbered stoppered colorimetric tubes. Add a certain amount of magnetic nano demulsifier prepared in Example 1 and Comparative Example 1 into the stoppered colorimetric tubes, respectively, and one tube without magnetic nano demulsifier is used as a blank control sample. Place these stoppered colorimetric tubes in a 60°C water bath and heat for 5 minutes, and shake them thoroughly within 1 minute to mix the magnetic nano demulsifier and diesel emulsion evenly. Take the concentration, demulsification time and demulsification temperature of the magnetic nano demulsifier as variables, and record the demulsification effects in different states. Use formula (1) to calculate the demulsification efficiency of diesel emulsion:
[0059] Where R (%) is the demulsification efficiency, c0 and c1 are the oil contents of the emulsion before and after demulsification, respectively.
[0060] When the demulsification time was 80 min and the demulsification temperature was 60 °C, the effects of two magnetic nano-demulsifiers at different concentrations on the demulsification efficiency were compared. Figure 4 shown. Figure 4It shows that when the concentration of the two magnetic nano-emulsifiers increases from 0 to 1000 mg / L, the demulsification efficiency gradually increases and finally tends to be stable. When the concentration is 600 mg / L, the demulsification efficiencies of the magnetic nano-emulsifier Fe3O4@PDA of Comparative Example 1 and the magnetic nano-emulsifier Fe3O4@PDA-EDEP of Example 1 are 77.82% and 99.28%, respectively. It can be seen that after further grafting modification with EDEP, the demulsification efficiency of Fe3O4@PDA-EDEP is increased by more than 20%. When the concentration is further increased, the demulsification efficiency of Fe3O4@PDA-EDEP is not improved, indicating that the concentration of the magnetic nano-emulsifier of Example 1 is 600 mg / L, which is the optimal demulsification concentration.
[0061] 4. The magnetic nano-emulsifiers prepared in Example 1 and Comparative Example 1 were subjected to a recovery test. After each demulsification experiment, the magnetic nano-emulsifier was recovered by magnetic separation, and the recovered product was ultrasonically cleaned with acetone for 10 min. Then, the magnetic nano-emulsifier was recovered by magnetic separation, and after washing 2 to 3 times, the magnetic nano-emulsifier was placed in a vacuum oven at 45°C and dried for 8 h, and the next demulsification experiment was repeated.
[0062] The demulsifier dosage of the recyclability experiment is 600 mg / L, the demulsification temperature is 60°C, the treatment time is 80 min, and the number of recycling times is 10 times. The demulsification effect of the emulsion treated multiple times by the magnetic nano demulsifier of Example 1 and Comparative Example 1 is as follows: Figure 5 shown. Figure 5 It shows that the demulsification efficiency of Fe3O4@PDA in comparative example 1 decreased from the initial 78.57% to 65.71% when it was recycled for the fifth time, and then became lower and lower, and dropped to 48.57% when it was recycled for the tenth time. The demulsification efficiency of Fe3O4@PDA-EDEP in Example 1 was further modified by EDEP, and was initially 99.45%, which was still greater than 99% when it was recycled for the eighth time, and only dropped to 88.98% when it was recycled for the ninth time. This is attributed to the adsorption of the oil phase components in the emulsion on the surface of the magnetic nano-demulsifier, which made Fe3O4@PDA-EDEP lose its demulsification effect. The biomimetic adhesion of polydopamine to EDEP can increase the grafting strength of the surfactant on the surface of the magnetic nanoparticles, so Fe3O4@PDA-EDEP still shows excellent recyclability, and the number of recycling times can reach 8 times, which reduces the production cost to a certain extent and is beneficial to environmental protection.
[0063] It should be understood that the various forms of processes shown above can be used to reorder, add or delete steps. For example, the steps recorded in this disclosure can be executed in parallel, sequentially or in different orders, as long as the desired results of the technical solution of this disclosure can be achieved, and this document is not limited here.
[0064] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present disclosure, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0065] The above is only a specific embodiment of the present disclosure, but the protection scope of the present disclosure is not limited thereto. Any person skilled in the art who is familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present disclosure, which should be included in the protection scope of the present disclosure. Therefore, the protection scope of the present disclosure should be based on the protection scope of the claims.
Claims
1. A method for preparing a magnetic nano-emulsifier, characterized in that: The following steps are involved: S1: dissolving polydopamine in a phosphate buffer to obtain polydopamine phosphate; mixing the polydopamine phosphate with Fe3O4, and stirring in the dark and under aerobic conditions to obtain a Fe3O4@polydopamine complex; S2: dissolving the Fe3O4@polydopamine complex obtained in step S1 in a phosphate buffer solution, then mixing with a block polyether, and stirring under ultraviolet light irradiation and aerobic conditions to obtain the magnetic nano-emulsifier.
2. The preparation method according to claim 1, characterized in that: The pH of the phosphate buffer is 8.3-8.
5.
3. The preparation method according to claim 1, characterized in that: The mass volume ratio of the polydopamine and the phosphate buffer in step S1 is 0.1-0.2 g:400 mL; Preferably, in step S1, the mass ratio of the polydopamine to the Fe3O4 is 1:1-3.
4. The preparation method according to claim 1, characterized in that: Step S1: After mixing the polydopamine phosphate and the Fe3O4, firstly ultrasonicate for 5 to 8 minutes, and then stir; Preferably, the stirring conditions in step S1 include: stirring at a speed of 100 to 300 r / min for 12 to 36 hours in the dark and in the presence of oxygen.
5. The preparation method according to claim 1, characterized in that: After the stirring, step S1 further comprises the following steps: washing the product obtained after the stirring with ethanol and water alternately three times, and then performing magnetic separation to obtain the Fe3O4@polydopamine complex.
6. The preparation method according to claim 1, characterized in that: The mass volume ratio of the Fe3O4@polydopamine complex to the phosphate buffer in step S2 is 0.1-0.3 g: 200 mL; Preferably, in step S2, the mass ratio of the Fe3O4@polydopamine complex to the block polyether is 1:1-3.
7. The preparation method according to claim 1, characterized in that: The block polyether is selected from at least one of polyol block polyether and polyamine block polyether.
8. The preparation method according to claim 1, characterized in that: The stirring conditions in step S2 include: stirring at a speed of 100 to 300 r / min for 1 to 3 hours under ultraviolet light irradiation and aerobic conditions; Preferably, after the stirring, step S2 further comprises the following steps: washing the product obtained by the stirring with ethanol and water alternately three times, and then performing magnetic separation to obtain the magnetic nano-emulsifier.
9. The magnetic nano-emulsifier prepared according to the preparation method according to any one of claims 1 to 8.
10. Use of the magnetic nano-emulsifier according to claim 9 in the treatment of oil-water emulsions.
Citation Information
Cited By
Polystyrene-polyether core-shell structure demulsifier and preparation method thereof
CN119931063A